Enhanced photocatalytic activity of coupled ZnO/SnO2 nanocomposite under visible light for the degradation of Quinalphos in aqueous solution (Indian Journal of Chemical Technology (IJCT), 2023)
Metal nanocomposite as photocatalyst plays a major role for treating organic and inorganic pollutants present in industrial effluent through photocatalytic process. In this study, the co-precipitation method has been demonstrated in the preparation of ZnO/SnO2nanocomposite. The catalytic behaviour of the ZnO/SnO2 is studied against Quinalphos pesticide under the illumination of direct sunlight at neutral pH. The photocatalytic performance of ZnO/SnO2nanocomposite is examined by loading 2 mg/L of the catalyst in 30 ppm of the Quinalphos solution to achieve 98 % degradation in thirty minutes. The structural and chemical compositional analysis of the prepared ZnO/SnO2nanocomposite has been characterised by X-ray diffraction pattern and FT-IR spectrum respectively. The morphological analysis of ZnO/SnO2 nanocomposite is done by scanning electron microscope (SEM). The UV-Visible absorption spectroscopy is used to examine the optical properties of ZnO/SnO2nanocomposite together with the photo degradation process of Quinalphos pesticide. The presence of oxygen vacancies and the fluorescence property of the prepared nanocomposite are detected by fluorimetric analysis. Degradation efficiency is estimated by COD and TOC measurements. Moreover, the stability and quality of the prepared ZnO/SnO2nanocomposite could be separated easily and utilised for multiple cycles with no change in its activity.